The Cost of Compliance with Product Standards for Firms in Developing Countries : An Econometric Study - Maskus, Keith E. (World Bank, Washington, DC, 2012)
Standards and technical regulations exist to protect consumer safety or to achieve other goals, such as ensuring the interoperability of telecommunications systems, for example. Standards and technical regulations can, however, raise substantially both start-up and production costs for firms. Maskus, Otsuki, and Wilson develop econometric models to provide the first estimates of the incremental production costs for firms in developing nations in conforming to standards imposed by major importing countries. They use firm-level data generated from 16 developing countries in the World Bank Technical Barriers to Trade (TBT) Survey Database. Their findings indicate that standards do increase short-run production costs by requiring additional inputs of labor and capital. A 1 percent increase in investment to meet compliance costs in importing countries raises variable production costs by between 0.06 and 0.13 percent, a statistically significant increase. The authors also find that the fixed costs of compliance are nontrivial-approximately $425,000 per firm, or about 4.7 percent of value added on average. The results may be interpreted as one indication of the extent to which standards and technical regulations might constitute barriers to trade. While the relative impact on costs of compliance is relatively small, these costs can be decisive factors driving export success for companies. In this context, there is scope for considering that the costs associated with more limited exports to countries with import regulations may not conform to World Trade Organization rules encouraging harmonization of regulations to international standards, for example. Policy solutions then might be sought by identifying the extent to which subsidies or public support programs are needed to offset the cost disadvantage that arises from nonharmonized technical regulations.